Correction: Garza-Lopez et al. Protocols for Generating Surfaces and Measuring 3D Organelle Morphology Using Amira. Cells 2022, 11, 65 - Edgar Garza-Lopez; Zer Vue; Prasanna Katti; Kit Neikirk; Michelle Biete; Jacob Lam; Heather K. Beasley; Andrea G. Marshall; Taylor A. Rodman; Trace A. Christensen; Jeffrey L. Salisbury; Larry Vang; et al. (Cells, 2023)
In the original publication [...]